Pemetaan konseptual peran agroforestri dalam pertanian berkelanjutan dan ekonomi sirkular - Cahyani, Sukma (Journal of Economics Research and Policy Studies, 2025)
Global challenges related to food security, environmental degradation, and resource constraints drive the need for innovation in agricultural systems. Conventional agricultural models often overlook ecological balance and resource efficiency, resulting in long-term negative impacts. This study aims to map the conceptual role of agroforestry in supporting sustainable agriculture and the circular economy. This study employs a qualitative approach, utilising a systematic literature review method. The results of the study indicate that agroforestry functions as a key link that integrates ecological, social, and economic aspects in agricultural systems. Agroforestry enhances soil health and fertility by increasing organic matter content, promoting nitrogen fixation, and reducing soil erosion, while optimising resource use through circular economy principles, such as the utilisation of organic waste and closed production cycles. The synergy between agroforestry, sustainable agriculture, and circular economy produces an environmentally friendly, productive, and socially and economically sustainable production model. Thus, agroforestry is a key strategy for addressing the challenges of future agricultural development, supporting food security, environmental conservation, and enhancing community welfare holistically.